Ductilisation of tungsten (W): Tungsten laminated composites. (December 2017) - Reiser, Jens; Garrison, Lauren; Greuner, Henri; Hoffmann, Jan; Weingärtner, Tobias; Jäntsch, Ute; Klimenkov, Michael; Franke, Peter; Bonk, Simon; Bonnekoh, Carsten; Sickinger, Sven; Baumgärtner, Siegfried; et al.
Abstract: Here we elucidate the mechanisms of plastic deformation and fracture of tungsten laminated composites. Our results suggest that the mechanical response of the laminates is governed by the plastic deformation of the tungsten plies. In most cases, the impact of the interlayer is of secondary importance. Severely cold-rolled ultrafine-grained tungsten foils possess exceptional properties in terms of brittle-to-ductile transition (BDT), toughness, and tensile ductility. The motivation for investigating laminated composites is to determine whether a bulk material can be made that retains the ductility of the thin tungsten foils. In this paper we analyse W-AgCu, W-Cu, W-V, and W-Pd laminates in their as-produced and annealed conditions (e.g. 10, 100 and 1000 h at 1000 °C (1273 K) in vacuum). The analyses comprise (i) the mechanical characterisation by means of three-point bending (damage tolerance), Charpy impact (BDT), and tensile tests (total elongation to fracture) as well as (ii) the in-depth analyses of the microstructure by means of scanning electron microscopy (SEM), transmission electron microscopy (TEM), and Auger electron spectroscopy (AES). W-Cu laminates (60 vol% W) show 15.5% total elongation to fracture in a tensile test at room temperature. Furthermore, the BDT of tungsten laminated composites occurs at a temperature that is several hundreds of Kelvin lower than the BDT temperature of the pure tungsten bulk counterparts. Finally, we present the successful fabrication of a 1000 mm long W-Cu laminated pipe and show its high heat flux performance. Fabrication studies of high heat flux components made of tungsten laminates, in which the laminates are used either as heat spreaders or structural pipes, are presented. Graphical abstract: Highlights: Mechanisms of plastic deformation and fracture of W laminates have been elucidated. Diffusion mechanisms in W-Cu, W-V, and W-Pd laminated composites have been identified. Properties after annealing for 10, 100 and 1000 h at 1000 °C (1273 K) have been determined. Three-point bending, Charpy impact, and tensile tests have been performed. Divertor components made of W laminates have been built and HHF tested in GLADIS.